Co-Delivery of Gemcitabine and Paclitaxel in cRGD-Modified Long Circulating Nanoparticles with Asymmetric Lipid Layers for Breast Cancer Treatment - Jing Zhang (Molecules, 2018)
Combination chemotherapy is a common clinical practice in cancer treatment. Here, cyclic RGD (arginylglycylaspartic acid) peptide was introduced to the surface of lipid/calcium/phosphate (LCP) asymmetric lipid layer nanoparticles for the co-delivery of paclitaxel (PTX) and gemcitabine monophosphate (GMP) (P/G-NPs). The sphere-like morphology of P/G-NPs displays a well-distributed particle size, and high entrapment efficiency and drug loading for both PTX and GMP, with a positive zeta potential. P/G-NPs were stable for up to 15 days. The cellular uptake of these cyclic RGD-modified nanoparticles was significantly higher than that of unmodified nanoparticles over 2 h incubation. Compared with the combination of free PTX and GMP (P/G-Free), P/G-NPs exhibited a longer circulation lifetime and improved absorption for PTX and GMP. Polyethylene glycol was responsible for a higher plasma concentration and a decreased apparent volume of distribution (Vz). Nanoparticles enhanced the drug accumulation in tumors compared with other major organs after 24 h. P/G-NPs nearly halted tumor growth, with little evidence of general toxicity, whereas P/G-Free had only a modest inhibitory effect at 16 mg/kg of GMP and 2.0 mg/kg of PTX. Increased levels of apoptosis within tumors were detected in P/G-NPs group by approximately 43.6% (TUNEL assay). When compared with GMP NPs, PTX NPs, and P/G-Free, P/G-NPs decreased expression of B-cell lymphoma-2 and B-cell lymphoma-extra large proteins, and increased expression of cleaved poly-ADP-ribose polymerase-1. Calreticulin expression in tumors also increased upon the co-delivery of PTX and GMP. The antitumor effect of P/G-NPs is more powerful than P/G-Free, GMP NP, or PTX NP alone, without obvious toxicity.